Single nucleotide polymorphisms of Toll-like receptors and susceptibility to infectious diseases. (14th April 2015) - Skevaki, C; Pararas, M; Kostelidou, K; Tsakris, A; Routsias, J G
Summary: Toll-like receptors (TLRs) are the best-studied family of pattern-recognition receptors (PRRs), whose task is to rapidly recognize evolutionarily conserved structures on the invading microorganisms. Through binding to these patterns, TLRs trigger a number of proinflammatory and anti-microbial responses, playing a key role in the first line of defence against the pathogens also promoting adaptive immunity responses. Growing amounts of data suggest that single nucleotide polymorphisms (SNPs) on the various human TLR proteins are associated with altered susceptibility to infection. This review summarizes the role of TLRs in innate immunity, their ligands and signalling and focuses on the TLR SNPs which have been linked to infectious disease susceptibility.